Interfacial Phenomena Involved in Talc Flotation and Depression - D. W. Fuerstenau; P. Huang (International Mineral Processing Congress, 2003)
Various factors that control the natural flotability of talc, including differences due to crystal face and edge effects, were delineated. For study of talc depression phenomena, dextrin was used as a model depressant. For the enhancement of talc flotation, dodecylammonium acetate (DDAA) was used as the collector. The interaction of DDAA with talc was assessed by flotation experiments and electrokinetic (zeta potential) measurements, from which the role of hydrophobic bonding can be demonstrated. The results presented in this paper provide useful information on how the crystal chemistry and surface chemistry control the electrical double layer, adsorption phenomena, wettability, and flotation behavior of talc in aqueous media.